Faktor-Faktor Penyebab Terjadinya Stunting Pada Balita Usia 24-59 Bulan di Desa Benua Baru Kabupaten Kutai Timur - Mila Apriliana Sobon; Risnawati; Widya Astutik; Dwi Hartati (PT Naureen Digital Education, 2023)
Background: The incidence of stunting in Indonesia in 2022 with a prevalence of 24.4%. The government's target for 2024 is for stunting to decrease to 14%. Stunting is a condition where a toddler has a length and height according to age with a Z-score of -3 SD to <-2 SD. Stunting can be caused by several factors, namely a history of LBW, exclusive breastfeeding, anemia in toddlers and eating behavior. Objective: to determine the factors that cause stunting in Benua Baru Village, East Kutai Regency. Method: This research is a quantitative research with a cross sectional design. This research was conducted in Benua Baru Village in July 2023. The population in this study was toddlers aged 24-59 months. Samples were taken using the Total Sampling technique, namely 38 toddlers. Results: There is a relationship between the history of LBW and the incidence of stunting (0.015), there is a relationship between the history of exclusive breastfeeding and the incidence of stunting (0.013), there is a relationship between anemia in toddlers and the incidence of stunting (0.015), and there is no relationship between eating behavior and the incidence of stunting ( 1,000). Conclusion: The results of the study show that there is a relationship between a history of LBW, exclusive breastfeeding and anemia in toddlers with the incidence of stunting.